Substitusi Batang Lunak Pada Produksi Pelet Katuk Depolarisasi Untuk Perbaikan Produktifitas Domba - Agik Suprayogi; Juang Gema Kartika; Edi Santosa; Arya Widura Ritonga (Jurnal Ilmu Pertanian Indonesia, 2022)
Depolarized katuk pellets (Sauropus androgynus) as a growth trigger in ruminants have been produced, but are constrained by the adequacy of leaf raw materials. This study aims to utilize the soft stems (BL) of the katuk plant as a substitute for leaf raw materials (D) as much as 15%, and its effect on the productvitas of rams growing. Katuk leaf pellets (100%) and pellets mixed between D (85%) and BL (15%) or DBL, were prepared through a depolarization process. The male rams (21) were divided into 7 groups, 3 heads each, with different pellet-giving treatments. The treatment was the control group, leaf pellets 5 g (D-5), 10 g (D-10), and 15 g (D-15), and also the DBL pellet group 5 g (DBL-5), 10 g (DBL-10), and 15 g (DBL-15) per head daily. Each sheep gets adequate treatment and feed for 3 months. TheDBL-15 and D-15 sheep group showed an improvement in the average percentage of growth in sheep body weight and carcass (p<0.05), which were 54% and 43%, respectively, as well as 74% and 43%, compared to the control group, which was only 46% and 40%. The application of DBL-15 pellets showed a greater percentage of fat deposits, which was 3.4% (p<0.05) than the administration of D-15 pellets, which was only 2.4% and the control group (2.1%). It was concluded that the 15% soft stem to the pellets is still very good as a substitute for the raw material of katuk leaves for the production of depolarized pellets. Keywords: carcass, depolarization, katuk, pellet, sheep